Investigating the Supply Chain Strategy for Stock Investment Decision Making: Theory Planned Behavior and Reasoned Action - Sadalia, Isfenti; Sinurat, Mangasi; Omar, Khatijah; Susanto, Agus; Ilham, Rico Nur (ExcelingTech, 2020)
Abstract— Stock Investment Decision involves both parties, i.e., individuals and organizations. The decision to buy or sell shares determined by attitude, subjective norms, and perceived control. However, three main factors are used to predict stock investment appropriately. In other ways, the value-added in-stock service is essential to investors. It aims to ensure the investors ease to use for gaining certainty and increase their trust in shares investment. Also, internet stock trading because it has a positive relationship with the behavioral intentions of stock investors. Also, the intention to behave requires communication interventions, including providing smart equipment, software that can do the calculation, and the availability of large data. We focus only on profit (price) with religion. This study suggests that government support through policies implemented by the government also needs to pay attention to the length of time of observation, both past, and future so that actual measurements can be made accurately.Keywords— Supply Chain Strategy, Stock Investment, Theory Reasoned Action, Planned Theory of Behavior, Investment Decision making.